Host and Guest Encounters in Peer-to-Peer Accommodation: Insights from Airbnb Hosts - Saveriades, Alexis; Christou, Prokopis A.; Farmaki, Anna (My University, 2019)
Peer-to-peer (P2P) accommodation has grown exponentially in recent years, transforming the accommodation sector. The rapid growth of Airbnb, the market leader of P2P accommodation networks, exemplifies their phenomenal boom. Considering the numerous benefits P2P accommodation offers to both hosts and guests, its growth is not surprising. On the one hand, P2P accommodation allows owners of properties to gain additional income by renting out unused rooms, apartments and/or houses (Fang et al, 2016), thus improving their standard of living. On the other hand, it extends the range of accommodation options for travellers (Dolnicar, 2017), offering convenience and efficiency (McNichol, 2015) and the opportunity for personal relationship development between hosts and guests (Belarmino, et al, 2017; Tussyadiah and Zach, 2017). Correspondingly, research on peer-to-peer accommodation has begun to proliferate. Nonetheless, little attention has been paid to host-guest encounters within P2P accommodation. An examination of host-guest encounters imparts insights on how value is co-created by the sharing practice in P2P accommodation. This study qualitatively examines host-guest encounters within P2P accommodation by drawing from 25 Airbnb host experiences. Findings reveal a heterogeneity in host-guest encounters, as the sharing practice is conditioned by the motive predisposing hosts to engage in P2P accommodation and the degree of interaction with guests. We make explicit a typology of host-guest encounters, which reflects the changing nature of P2P accommodation.
Keywords: Peer to peer accommodation; Airbnb; Hosts and Guests